Level of Knowledge on Sexual and Reproductive Health Rights Among the Teenage Mothers and Their Parents in Rwanda: A Comparative Cross-Sectional Study - Lutasingwa D; Favina A; Ochora M; Rukanikigitero JMV; Gutabarwa LT; Kagaba A; Kaggwa MM (Dove Medical Press, 2024)
Dan Lutasingwa,1 Alain Favina,2 Moses Ochora,3 Jean Marie Vianney Rukanikigitero,1 Louange Twahirwa Gutabarwa,1 Aflodis Kagaba,1 Mark Mohan Kaggwa4,5 1Department of Research, Health Development Initiative, Kicukiro District, Kigali City, Rwanda; 2Department of Psychiatry, Faculty of Medicine, Mbarara University of Science and Technology, Mbarara, Uganda; 3Department of Pediatric, Faculty of Medicine, Mbarara University of Science and Technology, Mbarara, Uganda; 4Department of Psychiatry and Behavioural Neurosciences, McMaster University, Hamilton, ON, Canada; 5Forensic Psychiatry Program, St. Joseph Healthcare, Hamilton, ON, CanadaCorrespondence: Dan Lutasingwa, Email dan@hdirwanda.orgBackground: Parents are the primary caregivers and influential figures in adolescents' lives. They play a crucial role in shaping their children's attitudes, beliefs, and behaviors regarding sexual reproductive health. A vast difference in knowledge between adolescents and their parents indicates failure in knowledge translation and is associated with sexual and reproductive consequences, such as teenage pregnancies.Methods: In this cross-sectional study between December 2020 and December 2021, 834 teenage mothers and their parents/guardians (n = 861) were enrolled from all five provinces of Rwanda. Knowledge of sexual reproductive health (SRH) rights was assessed, and the differences between the understanding of parents and their children were analyzed using Chi-square tests.Results: There were statistically significant differences for all the assessed aspects of SRH knowledge rights between parents and their teenagers (ie, on the age of consent, safe abortion, right to education for teenage mothers, understanding of financial responsibilities, and perceptions of legal consequences).Conclusion: There is a significant knowledge difference between the two generations regarding their understanding of SRH rights. It is recommended that future programming should devise innovative ways that bring together parents and their children to discuss sexual reproductive health rights, which will result in empowered children and teenagers in Rwanda. Also, awareness programs are needed to improve the knowledge gaps regarding SRH in the public by policymakers, NGOs, and educators.&#x00A0Keywords: teenage pregnancies, parents, Rwanda, sexual reproductive health, knowledge, adolescent mothers